2022
DOI: 10.25122/jml-2021-0184
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effect of Red Roselle (Hibiscus Sabdariffa) against different types of oral bacteria

Abstract: This study aimed to compare the antimicrobial effect of an aqueous extract Red Roselle calyx (RE), Chlorhexidine (CH), Amoxicillin-clavulanic acid (ACA), Tetracycline (Tet), and Metronidazole (Met)on Streptococcus mutans (S. mutans), Staphylococcus aureus (S. aureus) and Enterococcus faecalis (E. faecalis) bacteria. The bacterial inhibition zones (BIZ)of the RE (25, 50, 75, 100) mg/ml and CH solutions (0.2%, 2%) were determined using the agar well diffusion method. Additionally, the susceptibility of the teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…Some dentists prescribe metronidazole with Amoxicillin to cover most likely pathogens, particularly anaerobic microorganisms, which usually inhabit the oral cavity. [54] Other dentists prefer using co-amoxiclav to broaden the spectrum to include penicillinase-producing bacteria. This preparation combines Amoxicillin and clavulanic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Some dentists prescribe metronidazole with Amoxicillin to cover most likely pathogens, particularly anaerobic microorganisms, which usually inhabit the oral cavity. [54] Other dentists prefer using co-amoxiclav to broaden the spectrum to include penicillinase-producing bacteria. This preparation combines Amoxicillin and clavulanic acid.…”
Section: Discussionmentioning
confidence: 99%
“…This in vitro study evaluated the antibacterial interaction of the ciprofloxacin-amoxicillin combination versus S. aureus using the agar well diffusion technique, isobolographic statistical method, and the interaction index. The agar well diffusion method is widely used and accepted to determine the antimicrobial effect of drugs and natural extracts [12,13,[19][20][21][22]. S. aureus showed high susceptibility to ciprofloxacin.…”
Section: Discussionmentioning
confidence: 99%
“…This was an in vitro study performed in the Instituto de Investigaci on en Ciencias Médicas of the Departamento de Clínicas of the Divisi on de Ciencias Biomédicas of the Centro Universitario de los Altos of the Universidad de Guadalajara. The protocol was submitted and approved by the Colegio Departamental de Clínicas (Acta junio 21,[2021][2022]. The experiments were carried out according to the Handbook of Microbiology Laboratory Practices [10,11].…”
Section: Type Of Studymentioning
confidence: 99%
“…Furthermore, roselle extract was used to prepare fortified goat-milk yogurt with anti-diabetic potency due to increased α-glucosidase inhibitory activity ( 183 ). It was also reported that roselle extract could suppress the growth of Escherichia coli and coliform bacteria in vitro and could be used in dairy products as an antibacterial agent and natural food colorant ( 178 , 201 ). Additionally, roselle extract can be used to replace artificial red colorants in food because it contains water-soluble anthocyanins, which can be used as a natural color additive ( 202 ).…”
Section: Application Of Plant Extract In Food Productsmentioning
confidence: 99%